Choisir de choisir — croire en ce monde / To Choose to Choose— To Believe in this World - Bogue, Ronald (Cinémas)

(untitled) (Cinémas, 2006)
AbstractIn the philosophy of Pascal and Kierkegaard and the cinema of Bresson and Dreyer, Deleuze finds “a strange thought,” an “extreme moralism that opposes the moral,” and a “faith that opposes religion.” This thought may be described as an immanent ethics of “choosing to choose,” such that one may thereby “believe in this world.” Pascal’s wager and Kierkegaard’s leap of faith are usually treated as exclusively theological concepts, but Deleuze—by way of a Nietzschean adaptation of Pascal and Kierkegaard—sees these concepts as a means of understanding a specific mode of existence, in which one “chooses to choose,” and thereby commits oneself to the perpetual responsibility of choosing. In the work of Dreyer and Bresson, Deleuze discovers a cinematic counterpart of this philosophy of “choosing to choose,” a cinema in which apparently religious concerns actually manifest an immanent ethics of modes of existence. This cinema highlights the fundamental vocation of modern cinema, which is to make possible a “belief in this world.” The problem facing modern directors is that the world seems nothing but a bad film, a collection of predictable and empty clichés devoid of any possibility of genuine creativity. Modern cinema’s answer to this challenge is to disrupt conventional ways of seeing and disclose already present alternatives to those conventions, such that new possibilities of existence are suggested. In this way, modern cinema allows a revived “belief in this world.” No longer a world of clichés, the world as transformed through modern cinema is one in which new modes of existence are envisioned, modes based on an ethics of perpetually “choosing to choose.” This cinematic ethics finally provides a means of understanding the proper relationship between cinema and philosophy, both of which have a common purpose, even if they have separate spheres of activity.